Shaping a score: Complexity, accuracy, and fluency in integrated writing performances. (April 2019) - Plakans, Lia; Gebril, Atta; Bilki, Zeynep
The present study investigates integrated writing assessment performances with regard to the linguistic features of complexity, accuracy, and fluency (CAF). Given the increasing presence of integrated tasks in large-scale and classroom assessments, validity evidence is needed for the claim that their scores reflect targeted language abilities. Four hundred and eighty integrated writing essays from the Internet-based Test of English as a Foreign Language (TOEFL) were analyzed using CAF measures with correlation and regression to determine how well these linguistic features predict scores on reading–listening–writing tasks. The results indicate a cumulative impact on scores from these three features. Fluency was found to be the strongest predictor of integrated writing scores. Analysis of error type revealed that morphological errors contributed more to the regression statistic than syntactic or lexical errors. Complexity was significant but had the lowest correlation to score across all variables.